Effect of Hurricane Sandy on Health Care Services Utilization Under Medicaid. (16th May 2016) - Sharp, Mark J.; Sun, Mingzeng; Ledneva, Tatiana; Lauper, Ursula; Pantea, Cristian; Lin, Shao
Abstract: Objective: This investigation assessed changes in utilization of inpatient, outpatient, emergency department, and pharmacy services in the aftermath of Hurricane Sandy in 8 counties in New York affected by the storm. Methods: Medicaid data for enrollees residing in 8 counties in New York were used to obtain aggregated daily counts of claims for 4 service types over immediate, 3-month, and 1-year periods following the storm. Negative binomial regression was used to compare service utilization in the storm year with the 2 prior years, within areas differentially affected by the storm. Results: Changes in service utilization within areas inside or outside the storm zone were most pronounced over the 1-year effect period. Differences in service utilization by year were the same by storm zone designation over the immediate effect period for all services. Conclusions: Results are consistent with previous investigations demonstrating that some of the greatest effects of a disaster on health services utilization occur well beyond the initial event. One-year effects, combined with some 3-month effects, suggests that storm recovery, with its effect on health care services utilization, may have followed different paths in areas designated as inside or outside the storm zone. ( Disaster Med Public Health Preparedness . 2016;10:472–484)